Severe bleeding with subclinical oculocutaneous albinism in a patient with a novel HPS6 missense variant. Issue 12 (4th October 2018) - Han, Chen G.; O'Brien, Kevin J.; Coon, Lea M.; Majerus, Julie A.; Huryn, Laryssa A.; Haroutunian, Sara G.; Moka, Nagabhishek; Introne, Wendy J.; Macnamara, Ellen; Gahl, William A.; Malicdan, May Christine V.; Chen, Dong; et al.
Abstract : Heřmanský–Pudlák syndrome (HPS), a rare autosomal recessive disorder, manifests with oculocutaneous albinism and a bleeding diathesis. However, severity of disease can be variable and is typically related to the genetic subtype of HPS; HPS type 6 (HPS‐6) is an uncommon subtype generally associated with mild disease. A Caucasian adult female presented with a history of severe bleeding; ophthalmologic examination indicated occult oculocutaneous albinism. The patient was diagnosed with a platelet storage pool disorder, and platelet whole mount electron microscopy demonstrated absent delta granules. Genome‐wide SNP analysis showed regions of homozygosity that included the HPS1 and HPS6 genes. Full length HPS1 transcript was amplified by PCR of genomic DNA. Targeted next‐generation sequencing identified a novel homozygous missense variant in HPS6 (c.383 T > C; p.V128A); this was associated with significantly reduced HPS6 mRNA and protein expression in the patient's fibroblasts compared to control cells. These findings highlight the variable severity of disease manifestations in patients with HPS, and illustrate that HPS can be diagnosed in patients with excessive bleeding and occult oculocutaneous albinism. Genetic analysis and platelet electron microscopy are useful diagnostic tests in evaluating patients with suspected HPS. Clinical Trial registration: Registrar:ClinicalTrials.gov Website:www.clinicaltrials.gov Registration Numbers: NCT00001456 and NCT00084305.